2007
DOI: 10.1002/adfm.200600669
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterned Polypyrrole: A Combination of Electrical and Topographical Characteristics for the Stimulation of Cells

Abstract: Electrically conducting polymers such as polypyrrole (PPy) are important biomaterials in neural engineering applications, including neural probes, nerve conduits, and scaffolds for tissue and nerve regeneration. Surface modification of these polymers can introduce other valuable characteristics for neural interfacing in addition to electrical conductivity, such as topographical features and chemical bioactivity. Here, the patterning of PPy to create topographical cues for cells is reported. In particular, 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
181
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(181 citation statements)
references
References 45 publications
0
181
0
Order By: Relevance
“…It was observed that the anodic peak potential (Epa) values upon incorporation of NGF to the CP PPy was found to shift to more positive values, increasing the applied charge, and thereby indicating more deposition of PPy and NGF (Gomez et al 2007). Moreover, at higher current density, it was noticed that the amount of NGF incorporated was less than at lower current densities because of either slow diffusion or denaturing of the incorporated NGF when excessive current was applied (Gomez et al 2007). Kim et al (2006) have reported the incorporation of both collagen and NGF into PPy, and confirmed the activity of both biomolecules through the neurite outgrowth of PC12 cells.…”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the anodic peak potential (Epa) values upon incorporation of NGF to the CP PPy was found to shift to more positive values, increasing the applied charge, and thereby indicating more deposition of PPy and NGF (Gomez et al 2007). Moreover, at higher current density, it was noticed that the amount of NGF incorporated was less than at lower current densities because of either slow diffusion or denaturing of the incorporated NGF when excessive current was applied (Gomez et al 2007). Kim et al (2006) have reported the incorporation of both collagen and NGF into PPy, and confirmed the activity of both biomolecules through the neurite outgrowth of PC12 cells.…”
Section: Tissue Engineering Applicationsmentioning
confidence: 99%
“…This would provide for very intimate contact between cells and the CP (as depicted in figure 16), ensuring continuous electrical contact between the electrode and the tissue (Richardson-Burns et al 2007). Moreover, the topographical patterns can provide contact guidance cues to primary neurons (Gomez et al 2007). The surface roughness properties of the CP films can be tailored by modifying the CP synthesis temperature.…”
Section: Physical -Chemical Modificationsmentioning
confidence: 99%
“…Polypyrrole has demonstrated cell and tissue compatibility in vivo and in vitro [12,22,23]. Human umbilical vein endothelial cells demonstrated higher cell doubling times when cultured on polypyrrole composite substrates [24].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Conducting polymers (CPs) provide a unique microenvironment for proliferation and differentiation of cells. [18][19][20][21] The electronic and ionic characteristics of these electrochemically active polymers have been utilized in the generation of neuronal probes and biosensors. [22][23][24] The prospect of having such smart-electrode interface on flexible-stretchable substrates opens up a valuable gateway to monitor and control biological events.…”
mentioning
confidence: 99%